Systematic hybrid laparoscopic and endovascular treatment of median arcuate ligament syndrome: A single-center experience - Schneider, Michael; Longchamp, Justine; Uldry, Emilie; Corpataux, Jean-Marc; Kefleyesus, Amaniel; Halkic, Nermin (Frontiers in Surgery, 2023)
Background Median arcuate ligament syndrome (MALS) is caused by celiac trunk (CT) compression by the median arcuate ligament. Clinically, this pathology varies from postprandial pain (Dunbar syndrome) to a life-threatening hemorrhage because of a rupture of a gastroduodenal artery aneurysm (GAA). Due to the low prevalence of this disease, there is no standard management for MALS. Material and method This was a single-center, retrospective study of 13 patients. Two groups were identified on the basis of the initial clinical presentation: those operated for a GAA rupture (bleeding group—BG) and those operated electively for Dunbar syndrome (Dunbar syndrome group—DG). The primary endpoint was 30-day postoperative complications of a systematic laparoscopic release of the median arcuate ligament and stenting during the same procedure. Results Seven patients (54%) underwent elective surgery. Six patients (46%) underwent semiurgent repair under elective conditions post-embolization for GAA bleeding. The total operative time was longer in the BG (p = 0.06). Two patients in the BG suffered early major complications and needed reintervention, and those in the DG had a lower comprehensive complication index. No mortality was reported at 30 days. Overall median length of stay was 5 days (IQR: 3.5–15.3). Patients in the DG had a significantly shorter length of stay (p = 0.02). At 6 months, the primary and secondary CT stent patencies were 82% and 100%, respectively. There were no high-flow GAA recurrences. Conclusions A combined approach of laparoscopic release of the median arcuate ligament and stenting during the same procedure is feasible and safe, and this approach must be systematically discussed in symptomatic patients.